Estudo estrutural e geoelétrico em aquífero fraturado na região de Caçapava do Sul (RS) - Oliveira, Mariana Vieira Galvão de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The inherent structural complexity of fractured rock aquifers, which controls the groundwater accumulation and flow in restricted zones, lead to a high number of non-producing dry wells. The analysis of geomorphological features and indirect investigations allows the identification of favorable targets for groundwater exploitation, representing a rational procedure in villages and small towns far away from urban centers. This work deals with regional and local structural surveys coupled with electrical resistivity tomography data in order to identify favorable targets for groundwater exploitation for urban consumption in a fractured granite located in a small village six kilometers north of Caçapava do Sul city, southern Brazil. The structural control is manifested in the regional landforms and clearly conditions the orientation of main drainages. Based on this structural control, four parallel electrical tomography survey lines were performed in an area of interest for groundwater exploitation, followed by the generation of 2D inversion models and interpolation for the analysis of pseudo 3D models. The contact between the very thin superficial soil (regolith) and the underlying granite massif determines the existence of a regional free aquifer and the probable recharge of the fractured rock aquifer. In the 2D inversion models, abrupt variations of electrical resistivity related to locally recognized vertical fractures occur, although they do not show lateral continuity (out of plane). The analysis of the geophysical maps from 40 meters depth allows the recognition of three alignments of low resistivity (around 500  m) within a granite context where high values predominate (above 15,000  m). These alignments show a triple fracture intersection pattern also recognized in satellite images, which are highly favorable for groundwater accumulation and exploitation

A complexidade estrutural inerente em aquíferos fraturados, que condicionam o fluxo subterrâneo em zonas restritas, resulta numa elevada taxa de insucesso em perfurações de poços produtores de água. A análise de feições geomorfológicas e investigações indiretas prévias permitem a seleção de alvos favoráveis para captação subterrânea, uma alternativa racional em vilarejos distantes dos centros urbanos. Este trabalho aborda o uso combinado de levantamentos estruturais regionais/locais, seguido pela aplicação do método geofísico da Eletrorresistividade, a partir de linhas de tomografia elétrica, para seleção de pontos favoráveis a perfuração num aquífero fraturado em granito, com vistas ao abastecimento de um pequeno vilarejo distante 6km a norte da cidade de Caçapava do Sul, extremo sul do Brasil. O controle estrutural existente no maciço granítico é expresso na geomorfologia regional e claramente condiciona a formação de vales e a orientação de drenagens. Baseado neste controle, foram realizadas 4 linhas de tomografia elétrica paralelas, numa área de interesse para captação de água subterrânea, seguido pela geração de modelos de inversão 2D e interpolação para análise em modelos pseudo 3D. O contato entre o solo superficial pouco espesso e o maciço granítico condiciona a existência de aquífero livre regional e a provável recarga do aquífero fraturado. Nos modelos de inversão 2D ocorrem variações bruscas de resistividade elétrica relacionadas a fraturas verticalizadas reconhecidas localmente, embora lateralmente desconexas. A análise de mapas a partir de 40m de profundidade permite o reconhecimento de três alinhamentos de baixa resistividade (em torno de 500.m) num contexto granítico onde predominam elevados valores (acima de 15000.m), cuja conexão tríplice define um sistema de junta de fraturas, padrão reconhecido em alinhamentos de drenagem e altamente favorável a captação...
Keywords: Geologia estrutural; Aquiferos; Poços; Abastecimento de água; Geomorfologia; Água - Captação; Águas subterrâneas; Geofisica; Granito; Caçapava do Sul (RS)